The Role of Neuroprediction and Artificial Intelligence in the Future of Criminal Procedure Support Science: A New Era in Neuroscience and Criminal Justice - Zico Junius Fernando; Rosmanila; Laily Ratna; Achmad Cholidin; Bhanu Prakash Nunna (Yuridika, 2023)
Recent developments in the field of neuroimaging in the world of neuroscience, when combined with artificial intelligence and, more specifically, with the use of mechanical engineering, have resulted in the creation of brain reading technology that may soon be widely used in scientific fields in the world including detecting, for example, criminal lies. When used in forensic psychiatry, this approach can increase the precision of risk assessment and help determine areas where intervention can be most effective. Neuro prediction with artificial intelligence can be called AI. This neuroprotection is a method of predicting criminal behaviour by finding biomarkers of brain function that can indicate that someone is committing crimes in the future. Normative legal research or library legal research (library research), with a statute, conceptual, comparative, historical, or futuristic approach. The nature of the research used in this research is descriptive-prescriptive and uses content analysis. The result of this research is to dissect the development of AI Neuroprediction in forensic psychiatry and criminal justice with attention to this technology's legal and ethical implications and potential applications. In the future, AI neuroprediction may play an important role in integrating forensic psychology into the criminal justice system. Through in-depth analysis of neurological data, AI neuroprediction could assist in identifying behavioral patterns or tendencies that might influence a person's criminal propensity, thus enriching traditional forensic psychological evaluations. It may also contribute to creating more precise and personalized intervention strategies to prevent repeat crimes.